DAMPAK REBRANDING TERHADAP LOYALITAS KONSUMEN DENGAN BRAND IMAGE SEBAGAI VARIABEL MEDIASI: STUDI KASUS REBRANDING TWITTER MENJADI X - Laurentia Vionita Hendarjo; Kurnia Khafidatur Rafiah (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of rebranding on consumer loyalty, with brand image as a mediating variable—a case study on Twitter’s rebranding to X. A quantitative approach was employed, using a survey method by distributing questionnaires to 134 respondents. The collected data were analyzed using SmartPLS 4 software. The results indicate that rebranding does not have a direct effect on consumer loyalty. However, rebranding has a significant effect on brand image, and brand image, in turn, has a significant effect on consumer loyalty. The results of the indirect effect test, conducted using the bootstrapping method, also show that brand image significantly mediates the relationship between rebranding and consumer loyalty. Based on these findings, companies planning to implement a rebranding strategy are advised to focus on developing a positive, strong, and relevant brand image.